2014
DOI: 10.1016/j.cct.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming limitations in previous research on exercise as a smoking cessation treatment: Rationale and design of the “Quit for Health” trial

Abstract: Aerobic exercise has been proposed as a stand-alone or adjunct smoking cessation treatment, but findings have been mixed. Laboratory studies have shown that individual exercise sessions lead to decreases in withdrawal symptoms and cigarette cravings, but findings are limited by lack of follow-up and artificial settings. On the other hand, smoking cessation treatment RCTs have generally failed to show positive effects of exercise on smoking cessation, but have been plagued by poor and/or unverified compliance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The results of the present study are confirmed by other authors, who also noted a beneficial influence of aerobic exercises for smoking cessation [ 27 , 29 ]. This influence appears to be particularly significant in women, as the exercises improve the women’s physical fitness, the frame of mind and comfort, as well as counteracting withdrawal effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study are confirmed by other authors, who also noted a beneficial influence of aerobic exercises for smoking cessation [ 27 , 29 ]. This influence appears to be particularly significant in women, as the exercises improve the women’s physical fitness, the frame of mind and comfort, as well as counteracting withdrawal effects.…”
Section: Discussionsupporting
confidence: 91%
“…Physical activity is conducive to and enhances the chances of smoking cessation. Williams et al [ 27 ] and Gimenez et al [ 28 ] observed positive effects of aerobic training consisting of climbing double steps (15 cm high) at the incremental intensity of 10, 20, 30, 40, 50, and 60 climbs/min.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in in the online supplemental materials, the search identified 11 self-described randomized controlled pilot trials of interventions for smoking, diet, physical activity, or medication adherence. Williams et al (2014) is the design paper for an RCT for which Williams et al (2010) was the pilot study. The RCT’s status in clinicaltrials.gov is “completed,” although the results have not yet been published.…”
Section: Problematic Pilot Studiesmentioning
confidence: 99%
“…One effort in this direction is a recent study that used a lab-based scenario with high ecological validity to show that an acute bout of exercise can reduce cravings following concurrent stressors [ 19 ]. Similar attempts to collect data from real life for smoking and exercise behavior using ecological momentary assessment methods (EMAs) have also been observed in the recent literature [ 20 - 21 ]. However, the investigation of the effects of short bouts of exercise as a means to acutely manage cravings in real life and the long-term effects of this method on relapse rates has not yet been the focus of any study.…”
Section: Introductionmentioning
confidence: 97%